EFEK THRESHOLDINFLASI TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI INDONESIA - Adam Luthfi Kusumatrisna; Iman Sugema; Syamsul H. Pasaribu (Jurnal Ekonomi dan Pembangunan, 2025)
Recent research states that relationship between inflation and economic growth is not linear. When inflation exceeds threshold, it will negatively affect economic growth. This study aims to investigate a linear and non-linear relationship between inflation and economic growth in Indonesia using provincial panel data. Linear relationships are tested using a fixed effect panel while non-linear relationships use the threshold fixed effect panel. Linear relationship of inflation in Indonesia has a negative effect on economic growth as well as government expenditure ratio growth and population growth, while investment growth and economic openness growth have a positive effect on economic growth. When conducting non-linear test, inflation in Indonesia negatively affected economic growth when it exceeded 9,57 and 9.59 percent. Meanwhile, when inflation exceeds 5.09 percent, economic growth in Indonesia has slowed. Inflation control policies must still be done to reduce the adverse effects of inflation, because high and fluctuating inflation is not good for the economy. This study advises stakeholders such as Bank Indonesia (BI) and the Regional Inflation Monitoring and Control Team (TPID) to be cautious when inflation starts to exceed 5.09 percent and be alert when inflation exceeds 9.57 percent and 9.59 percent.